Kesan agihan zakat terhadap tahap keagamaan dalam kalangan mualaf orang asal di Pahang / Samihah Ismail - Samihah , Ismail (2018)
According to the Quran, converts are one of the groups who are eligible to receive the zakat. The objective of the distribution of the zakat to the converts is to increase their Islamic faith or to domesticate their hearts. This study discusses the concept of the converts and the concept of zakat distribution to them according to Islamic perspectives. This study also describes the format of zakat distribution to the indigenous converts in the state of Pahang. Apart from that, this study also analyzes the effects of zakat distribution towards the level of Islam of the indigenous converts in Pahang. This study utilizes library research and interviews for gathering data. Data from interviews were analyzed using thematic analysis technique. Results show that zakat distribution, for the purpose of increasing the Islamic faith of the indigenous converts through Kelas Bridged Dakwah (KBD), already existed. Nevertheless, it is found that the converts are still lacking in the aspects of faith, jurisprudence and morals. This shows that the implementation of KBD as a platform to increase Islamic knowledge, understanding and practices in the aspects of faith, jurisprudence and morals is not fully effective. Therefore, Majlis Ugama Islam dan Adat Resam Melayu Pahang (MUIP) has to improve the weaknesses and any shortage in the management of KBD so that the purpose of zakat distribution to the converts can be achieved.